2012
DOI: 10.1159/000342534
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and Pathophysiology of Eryptosis

Abstract: Suicidal erythrocyte death (eryptosis) is characterized by cell shrinkage, cell membrane blebbing, and cell membrane phospholipid scrambling with phosphatidylserine exposure at the cell surface. Eryptotic cells adhere to the vascular wall and are rapidly cleared from circulating blood. Eryptosis is stimulated by an increase in cytosolic Ca2+ activity, ceramide, hyperosmotic shock, oxidative stress, energy depletion, hyperthermia, and a wide variety of xenobiotics and endogenous substances. Inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 62 publications
2
113
0
6
Order By: Relevance
“…Heme is transformed to biliverdin by the enzyme heme-oxigenase (HO) (Maines 1988, Murray 2003, Kikuchi et al 2005. Red blood cell degradation is enhanced in oxidative stress and energy depletion (Lang et al 2012), and oxidative stress also stimulates HO gene expression, and thus increases the transformation of heme to biliverdin (Choi andAlam 1996, Schipper 2004). These findings suggest that birds with higher level of oxidative stress and lower level of energy would produce more biliverdin.…”
Section: Blue-green Eggshell Pigmentationmentioning
confidence: 99%
“…Heme is transformed to biliverdin by the enzyme heme-oxigenase (HO) (Maines 1988, Murray 2003, Kikuchi et al 2005. Red blood cell degradation is enhanced in oxidative stress and energy depletion (Lang et al 2012), and oxidative stress also stimulates HO gene expression, and thus increases the transformation of heme to biliverdin (Choi andAlam 1996, Schipper 2004). These findings suggest that birds with higher level of oxidative stress and lower level of energy would produce more biliverdin.…”
Section: Blue-green Eggshell Pigmentationmentioning
confidence: 99%
“…Some of these pathologies are highly prevalent in patients on hemodialysis (for example, inflammation and changes in vascular smooth muscles and endothelium, processes that accelerate arteriosclerosis) (21,22). Hypoxemia also impairs resilience against reactive oxygen species (ROS) and may increase erythrocyte apoptosis (eryptosis) (23). Noteworthy, in patients with CHF and sleep apnea, it was observed that not only the frequency but also, the time spent with SaO 2 ,90%, the hypoxic burden, is a predictor for hemodynamic stress (24).…”
Section: Introductionmentioning
confidence: 99%
“…Much evidence points out different environmental conditions, such as diabetes, sepsis and the Mediterranean anemia, chronic renal failure and other diseases may induce eryptosis. 9 In a number of clinical trials, erythrocyte was confirmed that the expectancy was decreased from normal 120 days to about 90 days in uremia. 10 It is also one of the important reasons of renal anemia, including the occurrence of eryptosis frequent.…”
Section: Discussionmentioning
confidence: 97%